Changes Occured In The Mandıbular Morphology Durıng The Treatment Of Class Iı Dıvısıon 1 Cases Wıth Cervıcal Headgear - Mustafa Ülgen; Hakan N. İşcan; Hakan Gögen (Galenos Yayinevi, 1990)
This study was performed with the purpose to investigate the changes especially in such regions as the condyle and the ramus of the mandible that could be the causes of alterations in the mandibular growth pattern during the treatment of skeletal and dental Angle class II division 1 malocclusions with cervical headgear. Cervical headgear group was consisted of ten subjects. with a mean age of 9.020 ± 1.28 years where 10 subjects with a mean age of 9.456 ± 0.28 years served as controls. Mean treatment period with cervical headgear was 1.95 ± 0.27 years and the control period was 1.87 ± 0.03 years. Study was carried out on the pre- and post- study cephalometric films of the subjects. Total superimpositions of the films have shown that the sagittal vector of the forward and downward maxillary growth was inhibited while the vertical vector was stimulated and the forward mandibular growth was statistically significant. In the treatment group ramal inclination, gonial angle and total mandibular length were all increased at a statistically significant level. The condyle remodelled downward in the control group while its vertical position remained unchanged in the treatment group.